2020
DOI: 10.1029/2020je006581
|View full text |Cite
|
Sign up to set email alerts
|

Intracrater Sediment Trapping and Transport in Arabia Terra, Mars

Abstract: Craters are the most prevalent basins and potential depocenters of sediment on Mars. Within these craters and extending from them, terminal dune fields and wind streaks are abundant, indicating active sediment transport and providing a way to study how wind and sediment interact with crater topography. Here we explore the role of craters as both sources and sinks in the modern Martian sedimentary cycle. Our results show that craters with low albedo wind streaks (indicative of sediment transport out of a crater… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 67 publications
1
3
0
Order By: Relevance
“…Mapping of wind streaks in Arabia Terra has also demonstrated that craters with layered mounds do not always have an adjacent wind streak (Fergason & Christensen, 2008). Furthermore, the duration of this N-S wind direction is not known and considered to be a recent characteristic of Arabia Terra (Dorn & Day, 2020;Fergason & Christensen, 2008). Thus, a vortex/eddy type of wind influence (Day et al, 2016) is more agreeable with our observations.…”
Section: Eroded Crater Infill Versus Forming As a Moundsupporting
confidence: 86%
“…Mapping of wind streaks in Arabia Terra has also demonstrated that craters with layered mounds do not always have an adjacent wind streak (Fergason & Christensen, 2008). Furthermore, the duration of this N-S wind direction is not known and considered to be a recent characteristic of Arabia Terra (Dorn & Day, 2020;Fergason & Christensen, 2008). Thus, a vortex/eddy type of wind influence (Day et al, 2016) is more agreeable with our observations.…”
Section: Eroded Crater Infill Versus Forming As a Moundsupporting
confidence: 86%
“…We measured orientations of these features and found them to be consistent across all sites in both craters with a formative wind direction to the northwest, assuming the “horns” of the crescents are oriented downwind (Figure S6 in Supporting Information ). This is markedly different from the modern wind regime in western Arabia Terra, which is dominated by winds to the south and southwest, inferred by wind streaks, modern barchan dunes, the orientation of eroded outcrops and yardangs, and Global Circulation Models (GCMs) (Dorn & Day, 2020; Edgett, 2002; Fenton & Richardson, 2001; Rodriguez et al., 2010; Silvestro et al., 2011). Alternatively, the orientation could be explained by recirculation within the crater inducing a reversed flow at the surface, allowing for a regional wind direction more similar to present‐day patterns.…”
Section: Discussionmentioning
confidence: 89%
“…In some areas the sources of sediment are easy to identify in visible images, such as in the north polar erg where sand is clearly seen to be eroding from within the north polar basal unit (Byrne and Murray, 2002;Massé et al, 2012;Tsoar et al, 1979;SOM 2). In other areas, it is likely that aeolian sands have been transported long distances (up to hundreds of kilometers) and may then be mixed with several sources within sediment "sinks," such as topographic lows (Dorn and Day, 2020).…”
Section: Wind-transported Sediment Compositionmentioning
confidence: 99%
“…The most extensive coverage of dune sand occurs within the northern circum-polar basins as nearly continuous sand seas (e.g., Olympia Undae) (Hayward et al, 2014;Lancaster and Greeley, 1990). Impact craters are the most wide-spread locale for dune fields because these serve as a natural sediment sink (Dorn and Day, 2020;Greeley et al, 1992;Hayward et al, 2007;2014;Roback et al, 2020). Other common settings for dune fields are topographic depressions such as troughs, valleys, and chaotic terrain, including the great structural rift system of Valles Marineris (Chojnacki et al, 2014a).…”
Section: Bedforms: Types and Morphologiesmentioning
confidence: 99%